Evidence for phylogenetic signal and correlated evolution in plant–water relation traits. Issue 2 (2nd December 2022) - Ávila‐Lovera, Eleinis; Winter, Klaus; Goldsmith, Gregory R.
Summary: Evolutionary relationships are likely to play a significant role in shaping plant physiological and structural traits observed in contemporary taxa. We review research on phylogenetic signal and correlated evolution in plant–water relation traits, which play important roles in allowing plants to acquire, use, and conserve water. We found more evidence for a phylogenetic signal in structural traits (e.g. stomatal length and stomatal density) than in physiological traits (e.g. stomatal conductance and water potential at turgor loss). Although water potential at turgor loss is the most‐studied plant–water relation trait in an evolutionary context, it is the only trait consistently found to not have a phylogenetic signal. Correlated evolution was common among traits related to water movement efficiency and hydraulic safety in both leaves and stems. We conclude that evidence for phylogenetic signal varies depending on: the methodology used for its determination, that is, model‐based approaches to determine phylogenetic signal such as Blomberg's K or Pagel's λ vs statistical approaches such as ANOVAs with taxonomic classification as a factor; on the number of taxa studied (size of the phylogeny); and the setting in which plants grow (field vs common garden). More explicitly and consistently considering the role of evolutionary relationships in shaping plant ecophysiology could improve our understanding of how traits compare among species, how traits are coordinated with one another, and how traits vary with the environment.